A new phenylthiourea grafted Mn-Anderson polyoxometalate cluster: Synthesis, crystal structure and characterization. (1st September 2018) - Zeng, Xianghua; Gong, Chunhua; Guo, Haiyang; Xu, Hao; Zhang, Junyong; Xie, Jingli
Graphical abstract: Taking advantage of the covalently grafted amino group of Mn-Anderson precursor, the asymmetric [N(C4 H9 )4 ]3 [MnMo6 O18 (OCH2 )3 CNHCSNHPh(OCH2 )3 CNH2 ] cluster consisting of phenylthiourea has been successfully achieved. Those clusters could be connected through H-bonding interactions of CH⋯O to form an infinite supramolecular chain and the adjacent 1D chains are linked by H-bonding interactions of NH⋯O to generate a 2D supramolecular layer. Abstract: A novel phenylthiourea modified Mn-Anderson polyoxometalate, [N(C4 H9 )4 ]3 [MnMo6 O18 (OCH2 )3 CNHCSNHPh(OCH2 )3 CNH2 ] (1 ) has been synthesized and characterized by IR, NMR, UV–Vis spectroscopy, thermogravimetric, electrochemical and single-crystal X-ray diffraction analysis. Structural analysis reveals that compound 1 crystallizes in the orthorhombic crystal system, space group Pcab with a = 17.7477(9) Å, b = 33.6245(16) Å, c = 32.322(2) Å, V = 19288.7(19) Å 3 and Z = 8. Noticeably, the asymmetric POM cluster with terminal modification could be connected through H-bonding interactions of CH⋯O to form an infinite supramolecular chain. Furthermore, the adjacent 1D chains are linked by H-bonding interactions of NH⋯O to generate a 2D supramolecular layer.